A new optimized configuration for capacity and operation improvement of CCHP system based on developed owl search algorithm - Yan Cao; Qiangfeng Wang; Zhijie Wang; Kittisak Jermsittiparsert; Mohammadreza Shafiee (Energy Reports, 2020)
One of the best ways to optimally consuming fossil fuel thermal energy is to utilize combined cooling, heating, and power (CCHP) systems. In such systems, by recycling heat wasted from hot gases simultaneously generating power, heat, and refrigeration from combustion, as well as water and cooling oil in electricity production systems, the overall system energy utilization efficiency can be increased to more than 85%. Analysis and optimization of the CCHP systems are mostly in accordance to the operating cost reduction without considering the emissions reduction and actual energy utilization. The present study proposes an energy flow for CCHP system to decrease the main power consumption based on a building thermal demand in Kerman area, Iran. The method introduced a developed version of the owl search algorithm to increase the efficiency of the CCHP system in comparison with the separation production system. Final simulations declare well efficient results for the presented method.
Keywords: 330; Capacity; Combined cooling heating and power system; Improved; Operation strategy; Owl search algorithm